KEBIJAKAN PENAL DAN NON PENAL PEMERINTAH DALAM PENANGGULANGAN TINDAK PIDANA PENODAAN AGAMA DI INDONESIA - Adnan, Idul (STIT Sunan Giri Bima, 2023)
Over the last 40 years, cases of religious blasphemy in Indonesia have almost had the same pattern. Therefore, the problem that will be raised in this article is related to the prevention of religious blasphemy carried out by the government, especially the police and other law enforcers. Based on its role and function, referring to the decree of the President of the Republic of Indonesia number 1/PNPS of 1965 concerning the prevention of abuse and/or blasphemy of religion, the police protect religion and religious practices that develop in society and protect every religious belief and practice carried out by its followers. In practice, there are many cases of religious abuse/blasphemy that are misleading to people who do not understand religion. The method used in this research is a normative legal approach, meaning that research is carried out by referring to legal norms that apply in society and those in positive law. With regard to the state's duty to guarantee religious freedom, especially the police as a law enforcement institution regulated in Article 156a of the Criminal Code.